Emerging Electric Machines Advances, Perspectives and Applications - Zobaa, Ahmed F.; Abdel Aleem, Shady H.E (IntechOpen, 2021)
This book is an introduction to the concepts and developments of emerging electric machines, including advances, perspectives, and selected applications. It is a helpful tool for practicing engineers concerned with emerging electric machines and their challenges and potential uses. Chapters cover such topics as electric machines with axial magnetic flux, asynchronous machines with dual power supply, new designs for electrical machines, and more.